2019
DOI: 10.4236/wjcd.2019.96035
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hypertension (HTN) in a Cardiology Department in Bamako (Mali): Financial Aspects

Abstract: Background: Studies on financial aspects of High blood pressure management are rare and old without differentiating categories of expenses. On the other hand there is an evolution in health system with the introduction of a medical insurance. Objective: We performed this study to estimate costs related to insurance status. Methodology: The prospective study on patients aged 15 years and older extended from 01 May to 31 August 2016 and was carried out in the cardiology department of the University Hospital Gabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Study characteristics are summarized in Table 1 , a more detailed version can be found in additional file 2 . Regarding the economic study design, 21 studies followed a partial economic evaluation (nine cost descriptions [ 33 , 35 – 38 , 44 , 47 , 49 , 56 ], eight cost analyses [ 41 , 45 , 46 , 48 , 50 , 57 , 58 , 64 ] and four cost-outcome descriptions [ 32 , 34 , 43 , 63 ]. The remaining studies followed a full economic evaluation design (seven cost effectiveness analyses [ 39 , 40 , 54 , 59 62 ], three cost utility analyses [ 42 , 51 , 52 ] and two cost minimization analysis [ 53 , 55 ]).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Study characteristics are summarized in Table 1 , a more detailed version can be found in additional file 2 . Regarding the economic study design, 21 studies followed a partial economic evaluation (nine cost descriptions [ 33 , 35 – 38 , 44 , 47 , 49 , 56 ], eight cost analyses [ 41 , 45 , 46 , 48 , 50 , 57 , 58 , 64 ] and four cost-outcome descriptions [ 32 , 34 , 43 , 63 ]. The remaining studies followed a full economic evaluation design (seven cost effectiveness analyses [ 39 , 40 , 54 , 59 62 ], three cost utility analyses [ 42 , 51 , 52 ] and two cost minimization analysis [ 53 , 55 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The timeframe for data collection ranged from 20 days to 18 months. For the cost calculation, most studies used medical records [ 32 – 35 , 38 , 45 , 47 49 , 54 – 57 , 63 ] or questionnaires and interviews [ 33 – 39 , 43 45 , 50 , 64 ]. Additional sources were price lists [ 41 , 46 , 47 , 49 , 51 , 54 , 57 59 , 62 ], facility records [ 34 , 39 – 41 , 43 , 46 , 52 , 53 , 56 , 64 ] and other literature such as studies on income in South Africa [ 59 , 65 ] or World Health Organization (WHO) reports [ 40 , 43 , 59 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations